Preparation of Arabic Language Environmental Program at Az-Zahra Lawang Islamic Boarding School - Aminata, Diah Dina; Junaidi, Muhammad Rifqi (LP2M of Institute for Research and Community Services - UIN Walisongo, 2024)
Language Environment is very necessary to support the habituation of students' speaking skills. Where students are conditioned to use Arabic in daily activities, so it requires the preparation of language programs that support this activity. The Arabic Language Environment Program is a teacher mentoring program of Az-Zahra Islamic Boarding School which is carried out periodically by involving teachers in educational activities. This activity aims to provide insight to teachers regarding the strategy and implementation of Arabic environmental programs that can be implemented in the Az-Zahra Islamic Boarding School. The implementation of this assistance uses the RRA (Rapid Rural Appraisal) method, while the method in its implementation uses the PRA (Participatory Rural Appraisal) technique where this method consists of the preparation stage, namely observation and interview, then the implementation stage, and ends with the evaluation stage. After the Assistance program, teachers who were initially passive in optimizing language activities became more active and creative, besides that other changes that can be observed are from the lack of information and awareness of teachers related to the urgency of the language environment to be aware of the importance of strategies and implementation of the Arabic language environment program to make students actively speak Arabic.